Skin microbiota signature distinguishes IBD patients and reflects skin adverse events during anti-TNF therapy - Reiss, Zuzana; Rob, Filip; Kolar, Martin; Schierova, Dagmar; Kreisinger, Jakub; Jackova, Zuzana; Roubalova, Radka; Coufal, Stepan; Mihula, Martin; Thon, Tomas; Bajer, Lukas; Novakova, Michaela; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Crohn’s disease (CD) and ulcerative colitis (UC) are two forms of inflammatory bowel disease (IBD), where the role of gut but not skin dysbiosis is well recognized. Inhibitors of TNF have been successful in IBD treatment, but up to a quarter of patients suffer from unpredictable skin adverse events (SkAE). For this purpose, we analyzed temporal dynamics of skin microbiota and serum markers of inflammation and epithelial barrier integrity during anti-TNF therapy and SkAE manifestation in IBD patients. We observed that the skin microbiota signature of IBD patients differs markedly from healthy subjects. In particular, the skin microbiota of CD patients differs significantly from that of UC patients and healthy subjects, mainly in the retroauricular crease. In addition, we showed that anti-TNF-related SkAE are associated with specific shifts in skin microbiota profile and with a decrease in serum levels of L-FABP and I-FABP in IBD patients. For the first time, we showed that shifts in microbial composition in IBD patients are not limited to the gut and that skin microbiota and serum markers of the epithelium barrier may be suitable markers of SkAE during anti-TNF therapy.